Natality effects on the elementary school population in Tuzla Canton - Kadušić, Alma; Smajić, Nedima (Journal for Geography, 2018)
The end of the 20th and the beginning of the 21st century in the area of Tuzla Canton is characterized by negative demographic trends such as decreasing birth rates, increasing mortality rates, decreasing natural change rates, aging population, decreasing total population, while adverse economic, social, political and other conditions after 1995 intensified economic emigration, mainly in the population between 20 and 40 years of age. As a result of such demographic trends, the aging process of the population has intensified in the post-war period, and this demographic process reverses the decline in potential biodynamics and population vitality. Due to the negative demographic trends in this area there has been a decrease in the population of elementary school age. The aim of this paper is to identify the main factors influencing this reduction, as well as the degree of their impact on this process, with particular emphasis on the natural dynamics of the population and the intensive population emigration. If no appropriate population policy activities are taken in the future, negative demographic trends may become even more expressed, which could adversely affect primary education in the municipalities of Tuzla Canton.
Keywords: Tuzla Canton; elementary school population; natality; aging; emigration